Experimental Study of Fly Ash Density Effect to the Mortar Compressive Strength with Recycled Fine Aggregate. (2017) - Sagara, Altho; Tjondro, Johannes Adhijoso; Putri, Dinda Karina
Abstract: Massive production of fly ash and recycled concrete aggregate from various sources such as industries, demolished buildings and so on has been seen as a threatening environmental waste from the conservative material engineering perspective. However, in recent years, the utilization of waste materials in mixed concrete have been turned upside down to become an alternative in producing eco-friendly construction materials. Therefore, this study is aimed to observe the mortar compressive strength that consists of cement, water, recycled fine aggregate and specifically fly ash whose amount is determined based on the packing density method. Several mixing variations are used to derive the correlation between fly ash density and mortar compressive strength. Three different fly ash percentages, which are 25% (loose), 35% (completely) and 45% (over) are used in the laboratory test with the variations of mixing ratios of 0.2, 0.35, and 0.5. The mortar under completely packaged condition delivers the highest compressive strength in any mixing ratio, which are found at 27.02 MPa, 30.26 MPa, and 32.15 MPa for respectively 0.2, 0.35 and 0.5 mixing ratio. Conclusively, this particular pattern indicates the suitability of packing density method usage as the basic to determine the optimum fly ash amount in mortar mixing.